Democratic Parenting of Single-Parent Men and Women in Instilling Social Interaction in Children - Harahap, Khodijah; Sahputra, Dika (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to determine how a single parent with a democratic parenting style instills social interaction in their child. This type of research is qualitative research data used in the study are the activities of democratic parenting of single-parent men and women related to children’s social interactions. This research was conducted in Makmur Hamlet, Padangrie Simatahari Village, Kotapinang Sub-District, South Labuhanbatu Regency, North Sumatra. This sample was taken using a purposive sampling technique. Data collection techniques in this study are observation, interviews, and documentation. Data analysis techniques are reduction, presentation, conclusion drawing, and verification. The results of this study show seven stages of the democratic parenting style, which include: agreeing to speak politely, using words such as please, sorry, and thank you, speaking in a low tone, using friendly expressions, mutual understanding, cooperation, openness, empathy, motivational support, and positivity. These stages involve agreeing to understand and support each other in decision-making, working together to maintain cleanliness and comfort, giving full trust to the child while correcting dishonest behavior, teaching the child to complement and embrace others, prioritizing life goals, avoiding toxic friendships, and encouraging independence and a sense of sufficiency while incorporating religious teachings. This research concludes that the parenting of male and female single parents has successfully educated children to interact well with their parents and the environment.